Analisa Pelanggaran Kode Etik Akuntansi Publik pada PT. Hanson Internasional Tbk - Doni Molana; Tengku Sheila Chairunisa; Darwin Darwin; Arwin Arwin; Putri Enzelina Nababan; Ancer Martati Ndraha; Rahima Br Purba (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze violations of the public accountant code of ethics that occurred in the audit of the financial statements of PT. Hanson International Tbk, especially in the 2016 report. In the report, the company recognized revenue of Rp732 billion from the sale of ready to build lots, even though the transaction was not supported by valid legal documents such as a sale and purchase binding agreement (PPJB). The financial statements still received a “fair without modification” opinion from the auditor, which then raises big questions regarding the integrity and competence of auditors in carrying out their duties. This case became a public concern because it affected thousands of investors, and triggered distrust of the company's audited financial statements. This research uses a descriptive qualitative approach with a literature study method, namely by examining various secondary sources such as scientific articles, audit reports, mass media news, and official documents from related institutions. The results of the study identified that the violations that occurred included the basic principles in the code of ethics for the public accounting profession, namely integrity, objectivity, competence and professional prudence, and professional behavior. These violations not only reduce the credibility of the public accounting profession, but also cause large financial losses to the public and tarnish the image of auditing in Indonesia. This research emphasizes the importance of strengthening supervision by regulators and professional organizations, implementing strict sanctions against ethical violations, and the need for early ethical character building through professional education and training. By strengthening the implementation of the code of ethics, it is expected that audit practices in Indonesia can run transparently, accountably, and professionally.